Discussion on the recruitment strategy for apheresis platelet donors in Chongqing during a public health emergency* - Cheng, Ying; Xie, Chengbing; Tian, Yunbo; Wang, Fang; Liu, Xingchen; Cheng, Danfeng (Frontiers in Public Health, 2024)
Objective This study aimed to analyze the population characteristics of apheresis platelet donors in Chongqing Province and provide a scientific basis for the development of precise and efficient recruitment strategies. The ultimate goal is to increase the number of regular platelet donors in preparation for public health emergencies. Methods This study involved 53,089 blood donors who donated apheresis platelets to the Chongqing Blood Center from 2020 to 2022. Data regarding age, sex, blood type, education level, occupation, and frequency of blood donation were collected and analyzed to identify factors influencing platelet donation. Results Between 2020 and 2022, the majority of apheresis platelet donors in Chongqing were aged 25–35 years, with a male-to-female ratio of 2.6:1. The ABO blood group distribution was O > A > B > AB. The apheresis platelet donors mainly consisted of college students, and the donors who had donated only once accounted for the greatest proportion. Conclusion Based on the population characteristics of apheresis platelet donors in Chongqing, blood collection and supply organizations must refine emergency blood collection and supply plans during public health emergencies. This study underscores the importance of developing precise and efficient recruitment strategies for apheresis platelet donors and expanding the pool of regular apheresis platelet donors. These measures are essential to ensure the timely, safe, and effective use of clinical blood resources during public health emergencies.